How to inspire customers via social media. Issue 6 (7th June 2020) - Sheng, Hong; Yang, Pianpian; Feng, Yuanyue
Abstract : Purpose: Social media has emerged as a new marketing channel and an important source for customer inspiration. Understanding the sources and consequences of customer inspiration via social media is important for both researchers and marketers. However, little has been done to empirically examine customer inspiration in the social media context. Specifically, the process through which customers become inspired and motivated by social media to purchase the advertised products remains elusive. Therefore, this study extends the conceptualisation of customer inspiration into the social media context, and explores the antecedents of customer inspiration from three perspectives: informational, social and personal. This study also examines the impact of customer inspiration on customers' behavioral intention. Design/methodology/approach: Survey methodology was used and data from 679 respondents were collected in China. To examine the hypothesized relationships, partial least squares (PLS) was used to analyse the data and Smart PLS 3.0 was used for data analysis. Findings: The study findings demonstrated that the vividness of ads, social influence and promotion focus had positive impacts on the "inspired-by state", and subsequently the "inspired-to state", which in turn positively influenced customers' purchasing intentions. However, media richness has a negative impact on the "inspired-by state". Originality/value: This study provides the first evidence of customer inspiration via social media and examines its antecedents and consequences. Practically, this study offers useful guidelines and suggestions for firms on how to inspire customers using social media.